2019
DOI: 10.1111/ropr.12332
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Autonomy: An Assessment of Policy Language for Highly Automated Vehicles

Abstract: Self-driving cars (also known as driverless cars, autonomous vehicles, and highly automated vehicles [HAVs]) will change the regulatory, political, and ethical frameworks surrounding motor vehicles. At the highest levels of automation, HAVs are operated by independent machine agents, making decisions without the direct intervention of humans. The current transportation system assumes human intervention though, including legal and moral responsibilities of human operators. Has the development of these artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…expert survey). A general criticism on this is made by Schuelke-Leech et al [30], Hubbrad [31], and Mackie [32]. Nevertheless, the problem seems to be far more complex.…”
Section: State-of-the-artmentioning
confidence: 99%
“…expert survey). A general criticism on this is made by Schuelke-Leech et al [30], Hubbrad [31], and Mackie [32]. Nevertheless, the problem seems to be far more complex.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The second is how these new autonomous agents are to be integrated into the current responsibility and liability regimes for driving. (Schuelke-Leech et al, 2019) Law enforcement [6] [11][18] Still, lawmakers have proposed and, sometimes, requested private companies to employ technical and organizational measures in order to guarantee the enforcement of the law. (Hacker, 2018) Path dependence resulting from capture by interest groups [18] Entrenched regulation of a legacy industry conflicts with the creation of a new industry, leading to regulatory path dependence resulting from capture by interest groups.…”
Section: Legal Issuesmentioning
confidence: 99%
“…Yet the matter of responsibility weighs heavily in the moral imagination of the public and policy makers…. For instance, the researchers found that people in Western cultures have a greater preference for saving children over the elderly than people from Eastern cultures (Schuelke-Leech et al, 2019) True values important to the diverse stakeholders [1] Tools such as the value-focused thinking approach (Keeney, 1994) would be useful in identifying and structuring societal objectives, thereby focusing on the true values important to the diverse stakeholders. (Barclay, 2014) Individual behavior/trace Congress and public administration lack expertise [3][15][16] The guide explicitly acknowledges that government does not hold all necessary expertise, and consequently needs the input from stakeholders.…”
Section: Cooperation Between Regulators [4]mentioning
confidence: 99%
See 2 more Smart Citations